Evaluation of germination and initial development of maxixe in the rainy period in agreste of Alagoas (Research, Society and Development, 2022)
The gherkin Cucumis anguria L. is originally from the African continent, cultivated in areas concentrated in tropical and subtropical climate regions, mainly in Brazil and the Caribbean. Gherkin is a vegetable that produces best in soils rich in organic matter, sandy, light and loose. The objective of this work was to evaluate the germination and initial growth of the gherkin plant as a function of different types of organic fertilizers. The project was carried out at the Arapiraca Agro-Food Technological Pole, located in the village of Bananeiras, located 12 kilometers from the municipality of Arapiraca, belonging to the State University of Alagoas. Irrigation consisted of drip irrigation to maintain field capacity. Initially, there was a mowing and a plowing to unpack the soil and a harrowing of the experimental area. Then, four 8 m long furrows were opened to mix the fertilizers. The experimental design consisted of subdivided plots containing four treatments and five replications, being studied three forms of manure in the plots, establishing the treatments: without manure, chicken manure, cattle manure and goat manure. The variables analyzed were: germination speed index, leaf length, leaf width, number of leaves and plant height. The gherkin germination occurred satisfactorily in the bovine fertilization and the fertilization with chicken litter contributed to a greater development in the length and width of the leaves, demonstrating the potential to be used as a fertilizer for this culture.